Pendekatan Pembelajaran Sosial Dengan Teknologi Pendidikan Dalam Mendukung Proses PAK Di Era Digitalisasi : Social Learning, Educational Technology, Christian Religious Education - Elsudarma Santi Helena; Chris Pasuhuk; Flowrent Natalia; Djoys Anneke Rantung; Noh Ibrahim Boiliu (Jurnal Penelitian Multidisiplin, 2022)
Social learning is a relatively new theory compared to other learning theories. Social Learning is learning through interaction with a community of experts and fellow learners. Communication between participants relies on social networking media such as online discussions, blogging, and text messages. As we know there are a lot of social media that exist today, based on data, there are 6 social media that are most often used by people, especially Indonesia, namely Facebook, Twitter, Google+, LinkedIn, Instagram, and Pinterest. To apply social learning we must pay attention to the features that can be used from each of these social media so that they can support a learning process. Then, determine which social media is suitable for the learning process you want to build. In Social Learning, there are many ways to interact between teachers and students with the presence of educational technology in the digitalization era. Likewise social learning with educational technology can support and be useful in supporting Christian religious education learning.